COMMUNCATIVE LANGUAGE TEACHING ITS COMPETENCE AND PRICIPLES - Uralov Islom Ural o’g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Along with Communicative language teaching, all the types of methods have their principles, competences, features which form them. CLT have 4 competences and 6 principles which are described in the article given below.